Behavioral effects of Aronia melanocarpa fruit juice in a rat model of ovariectomy-induced estrogen deficit - Antoaneta Georgieva; Milena Todorova; Miroslav Eftimov; Krasimir Kuzmanov; Stefka Valcheva-Kuzmanova (Folia Medica, 2022)
Introduction: The ovariectomized rat is a model used to mimic the changes in female organism during menopause. Aronia melanocarpa fruit juice (AMFJ) is extremely rich in phenolic substances (procyanidins, flavonoids and phenolic acids).Aim: The present study aimed to evaluate the effects of AMFJ on rat behavior in a model of ovariectomy-induced estrogen deficit.Materials and methods: Four groups of female Wistar rats were used, each consisting of 14 animals – sham operated (SO), ovariectomized (OVX), OVX+AMFJ5, and OVX+AMFJ10. After two-week recovery from the operation, three-month oral treatment was performed with distilled water for the SO and OVX groups, and AMFJ at doses of 5 ml/kg and 10 ml/kg for the OVX+AMFJ5 and OVX+AMFJ10 groups, respectively. Then, behavioral tests were conducted. Locomotor activity was assessed using the open field test (OFT). Anxiety was evaluated in the OFT, elevated plus-maze test and social interaction test. Depressive behavior was assessed in the forced swim test. Thermal pain sensitivity was measured in the hot plate test.Results: OVX rats showed increased anxiety, depressive behavior and pain sensitivity in comparison with SO animals. Compared to OVX rats, anxiety, depressive behavior, and pain sensitivity of AMFJ-treated animals were decreased. Locomotor activity of AMFJtreated rats was reduced in comparison with both SO and OVX animals, probably due to the sedative effect of the juice.Conclusions: AMFJ was able to antagonize the negative impact of the estrogen deficit on rat behavior (anxiety, depression, pain sensitivity), probably due to the biological activity of its polyphenolic ingredients.